Analisa Kerusakan Pada Sistem Kopling Mobil Toyota Rush Menggunakan Metode Uji Sem (Scanning Electron Microscope) - Junaidi; Yulfitra; N Syahputra (Cered Indonesia Institute, 2023)
The` powe`r tra`nsfe`r syste`m broa`dly consists of clu`tch u`nits, tra`nsmissions, de`fe`cts, on the` a`xis a`nd ve`hicle` whe`e`ls. While` the` position of the` clu`tch u`nit a`nd its compone`nts (clu`tch a`sse`mbly), is loca`te`d a`t the` front e`nd a`nd powe`r tra`nsfe`r syste`m on the` ve`hicle`. In a`ccorda`nce` with its fu`nction, na`me`ly to bre`a`k a`nd conne`ct, the` u`nit de`cide`s a`nd conne`cts the` flow of powe`r / motion / mome`nt from the` ma`chine` to the` powe`r tra`nsfe`r syste`m. The` ba`ckgrou`nd of the` a`u`thor in choosing the` title` of this stu`dy is du`e` to the` la`ck of knowle`dge` of ve`hicle` u`se`rs in ca`ring for the` clu`tch syste`m, so tha`t sma`ll da`ma`ge` will be` la`rge` a`nd will incre`a`se` the` cost of ma`inte`na`nce` a`nd re`pa`ir, disru`ption tha`t ofte`n occu`rs in the` clu`tch syste`m is we`a`r on the` clu`tch pla`te`, a`s we`ll a`s da`ma`ge` to the` compone`nt Othe`rs du`e` to la`ck of tre`a`tme`nt. This stu`dy u`se`s a` friction te`st me`thod. In the` re`su`lts of the` re`se`a`rch da`ma`ge` occu`rre`d in the` clu`tch syste`m is we`a`r a`u`s, we`a`k ple`nde`s, dry dra`gh tha`t ca`n ca`u`se` da`ma`ge` to the` clu`tch syste`m. The` ma`in fa`ctor tha`t ca`u`se`s da`ma`ge` to the` clu`tch syste`m is hu`ma`n e`rror or drive`r ofte`n u`se`s ha`lf a` clu`tch tha`t ca`n ca`u`se` da`ma`ge` to the` clu`tch syste`m a`nd ca`ble`. Su`gge`stions The` improve`me`nt is do not ofte`n u`se` ha`lf the` clu`tch a`nd do re`gu`la`r se`rvice`.